Mycophenolate Mofetil Hepatotoxicity Associated With Mitochondrial Abnormality in Liver Transplant Recipients and Mice. Issue 4 (October 2021) - Warren, Mikako; Mitsinikos, Tania; Yanni, George; Sasaki, Mika; Sasaki, Atsuo T.; Thomas, Dan
ABSTRACT: Objectives: Mycophenolate mofetil (MMF) is a widely used immunosuppressive agent. MMF hepatotoxicity has been reported in non-transplant and renal transplant patients with minimal histologic description. This is the first study describing detailed histology and ultrastructure of MMF hepatotoxicity. Methods: Four liver-transplant recipients (Cases 1–4) were suspected to have MMF hepatotoxicity. Cases 1–3 (two females and one male; 4–17 years) had multiple biopsies for liver function test (LFT) abnormalities. Case 4 (female; 16 years) had a surveillance biopsy. Electron-microscopic examination (EM) was requested on Cases 1–3 for unexplained, persistent LFT elevation and histologic abnormalities despite therapy and Case 4 for unexplained histologic abnormalities despite a stable clinical course. To confirm the pathologic changes in the human allografts, livers from MMF-treated and untreated mice were also reviewed. Results: While the allograft biopsies showed nonspecific histologic changes, EM revealed unequivocal mitochondrial abnormalities similar to those seen in primary and secondary mitochondrial disorders. In Cases 1 and 2, LFTs improved after stopping and reducing MMF, respectively. In Case 3, pre- and post-MMF treatment biopsies were performed and only the post-MMF biopsy demonstrated mitochondrial abnormalities. Mitochondrial abnormality in Case 4 was subclinical. The mouse study confirmed that MMF caused various stress changes in the mitochondria; number of mitochondria/cell (mean ± standard deviation; untreated group: 58.25 ± 8.426; MMF-treated group: 76.37 ± 18.66), number of lipid droplets/cell (untreated: 0.9691 ± 1.150; MMF-treated: 3.649 ± 4.143) and sizes of mitochondria (μm, untreated: 0.8550 ± 0.3409; MMF-treated: 0.9598 ± 0.5312) were significantly increased in hepatocytes in the MMF-treated mice compared with the untreated mice ( P < 0.0001). Conclusions: Although MMF is safe for the majority of patients, MMF can cause mitochondrial stress, which may trigger more severe mitochondrial abnormalities in a small subset. MMF hepatotoxicity should be considered for MMF-treated patients with unexplained, persistent LFT abnormalities and nonspecific histologic findings. EM should be requested for these cases. Abstract : Supplemental Digital Content is available in the text